Podwyżka taryfy autobusowej M.Z.K.G.G. (Gdańsk : [wydawca nieznany], 1949)
Afisz informujący o podwyżkach taryf 5.01.1949 r.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła